Development of a Self-Assessment Instrument to Measure Learner Motivation - Azizah, Nunung; Istiyono, Edi (Journal of Learning and Technology in Physics, 2024)
Learning motivation is crucial in the learning process. The motivation to learn will also be able to affect their academic abilities, and this will be one of the supporters of the success of the learning process. Judging from the importance of the function of learning motivation, the purpose of this study is to measure the level of learning motivation through self-assessment instruments with the aim of knowing how high learning motivation is in learning physics. The object of this research was the students of class X SMA 1 Kalasan, with a total of 60 respondents. This research is development research with a 4D design, namely define (definition), design (planning), develop (development, and disseminate). The data collection method in this study uses a questionnaire method with a Likert scale. Based on the results of the analysis, the self-assessment instrument has validity and is quite good with numbers above 0.330. And the reliability is quite high with the number 0.492. Based on this data, the self-assessment instrument can be said to be valid and reliable, so it is feasible to use it to measure the learning motivation of students.Keywords: Instruments; Self-assessment; Learning motivation